The institutional economics of water a cross-country analysis of institutions and performance - Saleth, R. Maria, 1955-; Dinar, Ariel, 1947-; World Bank.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2004)
This outstanding new book provides the most detailed and comprehensive evaluation of water reform and water sector performance from the perspectives of institutional economics and political economy.
1. Water challenge : an institutional diagnosis -- 2. Understanding institutions : nature, performance, and change -- 3. Existing literature : approaches, attempts, and limitations -- 4. Evaluating institutional linkages : towards an alternative methodology -- 5. Analytical framework and empirical models -- 6. empirical context : description and justification -- 7. Institutional changes in the water sector : a cross-country review -- 8. Institution-performance linkages : evidence and evaluation -- 9. Institution-performance linkages : robustness and contextuality -- 10. Institutional sequencing and packaging -- 11. Conclusions with implications for theory and policy.
"A co-publication with the World Bank."
Includes bibliographical references and index.
Keywords: Water-supply -- Economic aspects; Water-supply -- Political aspects; Water resources development -- Economic aspects; Water resources development -- Political aspects; Electronic books